KEMITRAAN DALAM PENGEMBANGAN EKOWISATA TANAH LOT DI KABUPATEN TABANAN PROVINSI BALI - , I PUTU ANANDA CITRA; , Dr. M. Baiquni, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The tourism development is affected by various components. Each component has different functions and roles. The importance of cooperation in tourism activities is a must to achieve the goal. Ecotourism is the direction of tourism development that is considered appropriate because, in essence, ecotourism can conserve and utilize natural and cultural community, far more stringent than just sustainable. This study is a review of Tourism Geography field entitled " Partnership In Development Of Tanah Lot Ecotourism In District Tabanan, Bali Province ". This research aimed to identify the parties acting in development of Tanah Lot ecotourism, analyze forms of partnership and contribution to the development of Tanah Lot ecotourism. This uses a geographic approach to the ecological approach to the theme of the analysis of interactions between humans and their environment activities related to tourism activity at Tanah Lot. Data were collected with a questionnaire and depth interviews with respondents who have been determined by proportional random sampling techniques and determination of key informants. Analysis of data using techniques of qualitative and quantitative descriptive analysis. For the contribution of partnerships in tourism development using scoring so it can be classified into three contributions of high, medium and low. The results showed that: 1) those who act in Tanah Lot ecotourism development that is local government, Village Office Beraban, Traditional Village Beraban, Business Actor Travel, Tourism Police, and Department of Transportation. 2) There are four forms of partnership based on the status of land ownership and program activities and resources that are used include management contracts, lease contracts, right to the building (RTB) and the concession contract. 3) Form partnerships management contracts, RTB, and contribute to higher concession contracts in tourism development while contributing to the rental contract of partnership in development of Tanah Lot ecotourism.